Manajemen Strategik dalam Perencanaan Peningkatan Mutu Pendidikan di Sekolah Dasar Islam Terpadu Cordova Samarinda - Yusniar Yusniar; Zaenab Hanim; Nurlaili Nurlaili (Journal on Education, 2023)
This study aims to determine the strategic management of improving the quality of education in the Integrated Islamic Elementary School of Cordova Samarinda. In this qualitative study, data were obtained through in-depth interviews with school principals, vice principals for curriculum, vice principals for student affairs and teachers. Data were collected by observation, interview and documentation methods and then analyzed using an interactive analysis model. The study results show that the school has analysed internal and external factors to determine a strategic program concerning eight national education standards and the unique educational standards of integrated Islamic school networks. These standards are reflected in work programs, including extracurricular programs and personality development programs for teachers and students. These programs are evaluated through supervision activities and school meetings to achieve common goals.